MATERNAL DEPRESSION AND CHILD OXYTOCIN RESPONSE; MODERATION BY MATERNAL OXYTOCIN AND RELATIONAL BEHAVIOR. Issue 9 (30th June 2015) - Pratt, Maayan; Apter‐Levi, Yael; Vakart, Adam; Feldman, Michal; Fishman, Ruth; Feldman, Tamar; Zagoory‐Sharon, Orna; Feldman, Ruth
Abstract : Background: Maternal postpartum depression (PPD) carries long‐term detrimental effects on children's well‐being, yet the mechanisms of transmission remain unclear. One possible pathway of vulnerability involves the oxytocinergic (OT) system, which is transferred from mother to child via sensitive caregiving and is disrupted in PPD. Method: A large birth cohort ( N = 1983) of women were repeatedly assessed for depression from birth to 6 years. Utilizing an extreme case design, two matched cohorts were formed; mothers chronically depressed from birth to 6 years and nondepressed controls ( N = 97, depressed = 41, nondepressed; N = 56). At 6 years, mothers and children underwent psychiatric diagnosis, urinary OT was assayed from mother and child before and after social contact, and mother–child interactions were coded. Results: Baseline OT and OT response of mother and child were interrelated and children of depressed mothers showed low baseline OT and attenuated OT response. Child OT response was negatively predicted by maternal depression, child Axis‐I psychopathology, maternal expressed negative affect, and child social withdrawal. Interaction effect of maternal baseline OT and depression emerged. Slope analysis indicated that when maternal OT was medium or low, child OT response was negatively impacted by maternal depression. However, when maternal OT was high, child OT was unaffected, suggesting that maternal OT functionality buffers the effects of depression on the child. Conclusion: Results suggest involvement of the OT system in the cross‐generational transfer of vulnerability, as well as resilience, from depressed mothers to their children. Because the OT system is open to interventions that enhance maternal touch and contact, findings have important implications for targeted early dyadic inventions.